(untitled) (Journal of Architectural Design, 2023)
In given article we will try to analyze of Islamic architecture and it`s evolution process. Moreover, we will try to clear up the role of Islamic architecture in formation Central Asian and Indian architecture. Lastly, we describe how Islamic buildings has been created and its development over the years, also, we have given evidence supporting our points.